Estudo fitoquímico, genético e atividade antifúngica do óleo essencial de Myrcia lundiana Kiaersk - Alves, Mércia Freitas (2017)
The objectives of this study were to characterize chemically the essential oils, to evaluate the genetic diversity and the antifungal activity of Myrcia lundiana plants collected in Serra de Itabaiana National Park, Areia Branca Municipality / SE. The essential oils of 23 plants of M. lundiana were obtained by hydrodistillation and analyzed by GC/MS-FID. Twenty-four compounds were identified in M. lundiana plants. Great chemical diversity was observed among the M. lundiana plants studied. Great chemical diversity was observed among the M. lundiana plants studied. The compounds found in greater quantity were nerolic, neral, geranial, isopulegol, iso isopulegol, 1,8-cineol and β-pinene, which defined the formation of three groups according to the chemical composition and cluster analysis. Genetic diversity was evaluated through the molecular marker ISSR, among 28 plants of a native population of the State of Sergipe. Thirty-five primers were tested, and 20 of them were polymorphic, resulting in 135 polymorphic and informative bands. The plants were divided into three groups by cluster analysis, the unweighted arithmetic mean and structure analysis. In the matrix of similarity of Jaccard there was variation of 0.15 to 0.87. Plants MLU-014 and MLU-015 presented low genetic diversity with similarity index of 0.87. On the other hand, pairs of plants MLU-007 and MLU-019, presented high diversity, with a similarity index of 0.15. The genetic diversity of M. lundiana plants is intermediate, and its expansion is necessary. The MLU-026 and MLU-028 plants are the most suitable for the conservation of this species. The antifungal activities of formulations based on essential oil of M. lundiana and their major compounds on phytopathogenic fungi Lasiodiplodia theobromae, Fusarium pallidoroseum, Fusarium solani and Colletotrichum musae were also evaluated. For the fungus F. pallidoroseum, the plants MLU-005 and MLU-019 provided 100% inhibition of mycelial growth from the concentration 1.1 mL/L (Minimum Inhibitory Concentration (MIC). For the plant MLU-022, MIC of 0.2 mL/L was observed, providing a better minimum fungicidal concentration (MFC) of 0.3 mL/L. For F. solani, the essential oils of the plants MLU-005 and MLU-019 presented MICs at the concentrations of 7.0 and 5.0 mL/L. The essential oil of plant MLU-022 had MIC of 0.5 mL/L, with MFC of 0.6 mL/L. Differentiated MIC was observed for the three studied chemotypes for fungus C. musae, ranging from 0.4 mL/L for chemotype MLU-005, 0.5 mL/L for chemootype MLU-022 and 0.7 mL/L for the MLU-019 chemotype, presenting better MFC for the MLU-005 chemotype of 0.5 mL/L. The essential oils of three M. lundiana chemotypes: MLU-005, MLU-019 and MLU-022 and the 1,8-cineol, isopulegol and citral (general + geranial) major compounds exhibited antifungal activity on the fungi tested. The essential oils of M. lundiana chemotypes and their major compounds have potential for the control of phytopathogens, and can be considered as an alternative to fungicides, since in lower concentrations they presented an inhibitory and fungicidal effect against these organisms.